2021
DOI: 10.1155/2021/6657533
|View full text |Cite
|
Sign up to set email alerts
|

Pneumothorax in Mechanically Ventilated Patients with COVID-19 Infection

Abstract: Data on patient-related factors associated with pneumothorax among critically ill patients with COVID-19 pneumonia is limited. Reports of spontaneous pneumothorax in patients with coronavirus disease 2019 (COVID-19) suggest that the COVID-19 infection could itself cause pneumothorax in addition to the ventilator-induced trauma among mechanically ventilated patients. Here, we report a case series of five mechanically ventilated patients with COVID-19 infection who developed pneumothorax. Consecutive cases of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
(22 reference statements)
0
22
0
Order By: Relevance
“…Another proposed mechanism entails pneumothorax secondary to pulmonary cyst rupture [ 13 ]. Pulmonary remodeling may develop before barotrauma from intubation or inflammatory processes such as COPD with emphysema, cystic fibrosis, tuberculosis, lung cancer, pneumocystis carinii pneumonia, lymphangioleiomyomatosis, Langerhans cell histiocytosis, and COVID-19 [ 14 , 15 ]. We also implicate the disruption of type II pneumocytes as predisposing one to spontaneous pneumothorax in COVID-19 since the virus enters cells through the angiotensin-converting enzyme-2, which is abundant in type II alveolar cells [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another proposed mechanism entails pneumothorax secondary to pulmonary cyst rupture [ 13 ]. Pulmonary remodeling may develop before barotrauma from intubation or inflammatory processes such as COPD with emphysema, cystic fibrosis, tuberculosis, lung cancer, pneumocystis carinii pneumonia, lymphangioleiomyomatosis, Langerhans cell histiocytosis, and COVID-19 [ 14 , 15 ]. We also implicate the disruption of type II pneumocytes as predisposing one to spontaneous pneumothorax in COVID-19 since the virus enters cells through the angiotensin-converting enzyme-2, which is abundant in type II alveolar cells [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Akdogan et al reported a case series of five mechanically ventilated patients with COVID-19 infection who developed pneumothorax. Three out of five patients died, suggesting pneumothorax to be a potentially fatal complication of the COVID-19 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the median hospital stay was 19.5 days, patients underwent invasive therapeutic methods, even though the collection of biological samples for respiratory microbiological cultures was decreased due to the risk of generating aerosols in hospital units. Therefore, the presence of infection is likely underestimated, especially due to the damage caused primarily by the virus, which promotes additional bacterial infections [ 8 ] and the formation of fibromyxoid exudates [ 73 ]. Likewise, the presence of pneumothorax has been associated with the appearance of pneumatoceles and bullae related to pneumonia, which are usually not observed in the early stages of the disease [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 ). Articles and case descriptions with as much information as possible were selected for analysis; therefore, not all case studies were selected [ [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] ...…”
Section: Methodsmentioning
confidence: 99%